Investigation on the synergetic effect between halide ions and internal corrosion inhibitor for HCl Acid and simulated NaCl sea water - Nur Alin, Mohd Azhari (2016)
This research is about investigation on the synergetic effect between halide ions and internal corrosion inhibitor (iCI) on hydrochloric (HCl) acid and simulated sodium chloride (NaCl) seawater. Halide ions have proven to be good corrosion inhibitor intensifiers in acidic media for steel and halides ions themselves acts as corrosion inhibitor.The study was done using immersion testing (weight loss test) to investigate the inhibition efficiency of three condition (H2O, HCl and NaCl) for two different soaking time (72 hours and 144 hours) and its synergestic effect with potassium iodide (KI) on the corrosion of low carbon steel in HCl and NaCl solution. The inhibition efficiency increase with the presence of KI. The iCI was characterized using fourier transform infrared (FTIR) spectroscopy and shown that C-O, OH, -COOH, C-N and NH functional group are present. The viscosity of iCI as tested using Brookfield viscometer is 673.4 cP.